Population structure of the fungus Sclerotinia sclerotiorum in common bean fields of Argentina - Aban, Carla Luciana (2021)
S. sclerotiorum is the causal agent of the white mould disease on common bean crops, one of the most threatening fungal diseases occurring across major bean production regions. Currently, there are no commercial cultivars with high levels of genetic resistance to white mould. The aim of this study was to analyse the population structure of 109 isolates of S. sclerotiorum from six dry bean fields in the main production area of Argentina using nine microsatellite loci. A total of 30 multilocus haplotypes (MLHs) were identified, of which 18 MLHs were unique. The remaining 12 MLHs were constituted by 83% of the isolates, six MLHs of which (composed of 75 isolates) were shared at least between two locations. Population genetic structure analysis and discriminant analysis of principal components (DAPC) identified two genetic clusters (subpopulations). The genetic cluster 1 (GC 1) was composed of 21 isolates and 15 MLHs. Similarly, the genetic cluster 2 (GC 2) was composed of 23 isolates and 15 MLHs. These two genetic clusters were observed in most locations sampled. Low levels of genetic differentiation (ΦST = 0.198; P < 0.0001) followed by high levels of gene flow (Nm > 1) between genetic clusters were observed. Linkage disequilibrium analysis showed that one of the two genetic subpopulations was under linkage equilibrium (P > 0.001), which is consistent with recombinant populations. These results suggest the occurrence of both modes of reproductive behaviour, clonal and recombining, compromising the durability of management strategies for white mould disease in common bean cultivars.